Involving, Countering, and Overlooking Stakeholder Networks in Soft Regulation: Case Study of a Small-to-Medium-Sized Enterprise's Implementation of SA8000. Issue 6 (July 2022) - Abboubi, Manal El; Pinnington, Ashly H.; Clegg, Stewart R.; Nicolopoulou, Katerina
To achieve effective stakeholder governance in the context of international social accountability certification (SA8000) requires constructing a network of agreement. In a case study of a small-to-medium-sized enterprise (SME), we examine managers' attempts at enrolling participants in the supply chain to investigate how they strive to engage these stakeholders. We adopt actor-network theory (ANT) and sensemaking theory to develop a novel approach to understanding social accountability (SA) standards' certification in stakeholder networks. We argue that the design and operation of any SA standard across a network requires not only attempts at enrolling other participants in the supply chain but management contextualizing and problematizing the terms of their involvement.